Gender differences in spousal caregiver strain and paid service use among dementia caregivers in rural Appalachia - Savla, Jyoti; Roberto, Karen A.; Fontaine, Leslie A. (Frontiers in Public Health, 2025)
Spousal caregivers of persons living with dementia (PLwD) often experience high overload and loneliness due to the intensive and ongoing nature of caregiving for their partner. Paid in-home services, such as assistance with daily household tasks, respite care, or personal care, might help ease caregivers' physical strain; however, it is unclear if these in-home services effectively address loneliness and overload and whether their benefits differ by gender. Guided by the Stress Process Model, we analyzed structured interview data from 61 spousal caregivers living in rural Appalachia. Although husbands reported significantly lower loneliness and overload than wives, the overall use of paid services was similar across husbands and wives. Among those experiencing high stress, however, a higher percentage of husbands used in-home paid services than wives. Logistic regression analyses revealed that greater emotional strain (overload and loneliness) and higher functional impairment of the PLwD were independently associated with increased likelihood of paid service use. Our findings underscore the need for programs and policies to acknowledge emotional strain as a legitimate criterion for eligibility for paid services.